THE MORBIDITY PATTERN OF GERIATRIC AGE GROUP PATIENTS ADMITTED IN MEDICINE WARD THROUGH EMERGENCY - SAMANTA, TIASH; SAHA, SATYENTRA NATH; SAHU, BADAL KUMAR; BISWAS, UTTAM; SARKAR, NABAKISHOR; SETH, SATYAPRIYA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Geriatric patients have higher admission rates, readmission rates, mortality rates, and emergency department attendance rates as compared to younger patients. They suffer from multiple comorbidities. Hence, the current study aims to find out the common causes of emergency hospital admission of geriatric populations and to describe their morbidity pattern. Methods: A total of 208 geriatric patients were included in the study. After taking proper consent from the caregiver/relative; the detailed history of the patient had been taken, along with clinical examination had been done at bedside. Then relevant laboratory investigation (Biochemical, Pathological and Radiological) had performed. Statistical analysis was done according to the study parameter. Results: System-wise morbidities did not vary statistically among the participants of different age groups. Among the elderly population (>80 years) endocrinal morbidities (93.9%) followed by gastrointestinal morbidities were the most common (91.8%). On the other hand, among the relatively younger age group, that is, 60–70 years psychiatric morbidities were least common (18.3%). Among the morbidities noted, central nervous system (CNS) morbidities had a female preponderance, which was statistically significant. All the participants who were smokers were diagnosed with endocrinal morbidities. While among non-smokers 83.7% had endocrinal morbidities. The difference was statistically significant (p<0.001). All the participants who were chronic alcoholics were diagnosed with GI morbidities. While among non-alcoholics 81.9% had Endocrinal morbidities. The difference was statistically significant. Conclusion: The elderly persons have significantly higher admission rates, mortality rates, and ICU admission rates. Social, economic, and healthcare support for the elderly people can be effective in reducing morbidities and unwanted clinical outcomes.